O stress no trabalho do docente da Pós-Graduação - Díaz Dextre, Katia Miluska (2021)
The general objetive was to investigate psychodynamics of stress and possible implications for the health and subjetivity of professors in a Graduate Program at renowned public university. We started the hypothesis and the existence of professors with stress and how this condition could lead to psychological suffering and health problems. The specific objetives were: Identifying existence of stress or the absence of stress, and in which phases (alarm, resistance, near, exhaustion and exhaustion); identifying existence of positive indices of common mental disorders or the absence of common mental disorders; characterizing the daily work, the existence of pressures, conflicts related to the demands of the management model and work evaluation; raise data indicative of the intensification of professor work. Also, Questionnaire and Semi-structured Interviews were used as methodological instruments. The Questionnaire was applied to 24 professors and it includes the Stress Symptoms Inventory (ISSL), the Self Report Questionnaire (SRQ-20) and questions about work, health and family life. The Semi-structured interviews were carried out with 7 professors and dealt with the theme of stress at work. Stress was found in 33.33% of the sample. After, analyzing the questionnaire data, commented summaries of the interviews and analysis of Categories A (Intensified work) and B (Suffering, stress and illness) were presented. We conclude that stress on teachers is characterized by biopsychic wear related to intensified work and the institutional dynamics of the university.